Implementation of Simple Additive Weighting (SAW) and Weighted Aggregated Sum Product Assessment (WASPAS) Methods in Selection of Young Lecturers with Achievements - M Mesran; Nelly Khairani Daulay (IJISTECH (International Journal of Information System and Technology), 2021)
Lecturers are resources owned by the University. One of the efforts to improve the quality of lecturers is by giving appreciation in the form of rewards or awards to the best lecturers or lecturers who excel. However, to be able to provide these rewards, of course there are several assessments that will be given to lecturers. The problem is how to give the assessment so that the lecturer is declared worthy to receive a reward or award. There is a decision support system or abbreviated as DSS where in the system there are several methods that can be used to provide an assessment of course with the determined assessment criteria. In this research, the method used is the Simple Additive Weighting (SAW) and Weighted Aggregated Sum Product Assessment (WASPAS) with several criteria into consideration. The results showed that alternative A3 and A2 were selected as outstanding young lecturers.